International Efforts to Save Healthcare Personnel during COVID-19 - Mohamed, Kawthar; Rezaei, Nima; Rodríguez-Román, Eduardo; Rahmani, Farzaneh; Zhang, Hongbo; Ivanovska, Mariya; A. Makka, Sara; Joya, Musa; Makuku, Rangarirai; Md Shahidul Islam; Nesrine Radwan; Laila Rahmah; et al. (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus disease 2019 (COVID-19) pandemic is a global challenge. Several governments of the world have decided to take drastic actions in order to combat the spread of the disease, including the closing of air, maritime and land borders, as an extreme measure of isolation of each country/region. However, such measures had not prevented the disease from spreading globally; as COVID-19 has already spread in almost all countries. This virus's main victims are the healthcare personnel (HCP), who are physically and psychologically affected. The HCP serves as the first line of defense against this pandemic, what if we faced a significant loss in their number? And what if our HCP was going through a deep dark depression? The condition would be terrifying not only for now but also in the future. This raises the need for an intensified International collaboration, that mainly supports the HCP.We are throwing by challenging moments, and it is clear that social distancing, cooperation, hygiene awareness and abide by the recommendation and help of all governments, as well as obtaining the support of international organizations could be an excellent tool for preventing an increase in the number of cases, principally in countries and regions were COVID-19 is in the early stage of the epidemic. However, this is not the final solution for the current pandemic. An intensified global program, which mainly supports the HCP, then considers the other aspects of the COVID19 pandemic might bring this pandemic to a peaceful end.